2016
DOI: 10.2298/psi1602199h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hexagonal and spherical model of vocational interests in the young people in Serbia and Bulgaria

Abstract: The aim of this study was to validate Holland's hexagonal and Tracey's spherical model of vocational interests in young adults in Serbia and Bulgaria. To this end, 1250 participants, 560 from Serbia and 690 from Bulgaria, filled in Serbian and Bulgarian versions of the Personal Globe Inventory (PGI, Tracey, 2002). Hubert and Arabie's randomization test of hypothetical orders, multidimensional scaling with fixed coordinates, Myors test and exploratory factor analysis were used. The results showed that the hexag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…The PGI has been used increasingly for assessing the structure of vocational interests in many countries and has shown a strong stability across various socio-cultural contexts (e.g., Darcy, 2005;Etzel, Nagy, & Tracey, 2015;Šverko, 2008). For example, recently, Hedrih, Stošić, Simić, & Ilieva (2016) examined the fit of the hexagonal and the spherical models of the PGI to Serbian and Bulgarian data. According to their findings, the models fit the data of both countries well, supporting the internationalization of the PGI.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The PGI has been used increasingly for assessing the structure of vocational interests in many countries and has shown a strong stability across various socio-cultural contexts (e.g., Darcy, 2005;Etzel, Nagy, & Tracey, 2015;Šverko, 2008). For example, recently, Hedrih, Stošić, Simić, & Ilieva (2016) examined the fit of the hexagonal and the spherical models of the PGI to Serbian and Bulgarian data. According to their findings, the models fit the data of both countries well, supporting the internationalization of the PGI.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Research studies conducted in the region of South-East Europe (Croatia, Serbia, Bulgaria) so far have confirmed both the validity of the hexagonal and the spherical models and that their structures are almost identical, especially between Serbia and Croatia (Hedrih 2008;Hedrih, Stošić, Simić, & Ilieva 2016;Šverko 2008b). On the other hand, review of the literature yielded no data on the functioning of these theoretical models in the Republic of Macedonia, or of Macedonian versions of these instruments, so the results of this study would be of particular use to practitioners and researchers working in Macedonia in the areas that include assessment of vocational interests and career counselling in general.…”
Section: Introductionmentioning
confidence: 79%
“…However, several studies suggested that Holland's hexagonal model does not replicate well across cultures (e.g., du Toit & De Bruin, 2002; suggesting that indigenous interest structures should be considered (Einarsdottir, Eyjolfsdottir, & Rounds, 2013). A more recently developed spherical model of interests and its measurement instrument called the Personal Globe Inventory (PGI; Tracey, 2002) seem to replicate quite well across cultures and were validated in various socio-cultural contexts, such as in Japan, Serbia, or Bulgaria (Hedrih, Stošić, Simić, & Ilieva, 2016;Long, Watanabe, & Tracey, 2006). A study having investigated the measurement equivalence of the PGI across Switzerland and Burkina Faso has shown that the PGI did reach configural and metric equivalence but not scalar equivalence, suggesting that culture specific norms should be considered (Atitsogbe et al, submitted).…”
Section: Methodological Implicationsmentioning
confidence: 99%